Implementing Same Day Discharge Following Percutaneous Coronary Intervention: A Process Evaluation. Issue 1 (January 2019) - Chen, Yingyan; Lin, Frances; Marshall, Andrea
Abstract : Background: The safety and effectiveness of same day discharge (SDD) following percutaneous coronary intervention are well demonstrated; however, the uptake of this model of care is low. Purpose: The aim was to examine the effectiveness of implementing SDD using a process evaluation methodology. Methods: This study was undertaken in a cardiac services department of a tertiary teaching hospital in southeast Queensland, Australia. It was anticipated before the implementation that 120 patients could be discharged the same day in a 6 months' time period. Patient selection process and guideline adherence were assessed along with patients' and relatives' satisfaction. Results: During implementation, 22 patients were discharged home the same day. It was found that staff did not follow the guideline consistently, with an overall adherence of 77.3%. Conclusion: The uptake of SDD was low in this implementation. The study is important as it provides direction for future improvement both in the criteria and the implementation process. Abstract : Supplemental Digital Content is Available in the Text.